Produktivitas Air Pada Sistem Irigasi Tetes Untuk Tanaman Hidroponik Caisim (Brassica chinensis var. Parachinensis) Dengan Berbagai Ukuran Polybag Dan Media Tanam Yang Berbeda - I Gde Darmaputra; Muhammad Idrus; Suprapto Suprapto (Jurnal Penelitian Pertanian Terapan, 2022)
his research was conducted in a plastic house at the Lampung State Polytechnic from June to October 2022. The study was a factorial experiment consisting of two factors with a randomized block design. The first factor is the type of planting media with 4 kinds, such as cocopeat, husk charcoal, sand, and soil. The second factor is the polybag size, such as small, medium, and large sizes. Each factor or treatment was repeated 3 times. The tools and materials used are drip irrigation, digital scales, polybags, pearl NPK fertilizer and caisim seeds. The objectives of the study were (1) to measure the growth and production of caisim plants on various planting media and polybag sizes, (2) to measure the amount of irrigation water used, and (3) to calculate the water productivity of caisim plants. The observed variables included crop production, amount of water use, and water productivity. Data analysis using ANOVA at the 5% significant difference test level. The results showed that there was no interaction between the type of planting media and the size of polybags, but the response in the treatment between types of planting media and between polybag sizes was significantly different. The type of media significantly affected the number of leaves, plant height, production, and water productivity of hydroponic caisim plants using a drip irrigation system. Polybag size did not significantly affect the number of leaves, plant height, production, and water productivity of hydroponic caisim plants using a drip irrigation system. In hydroponic caisim cultivation using drip irrigation, cocopeat growing media gave an average number of 9.8 leaves, plant height 34.4 cm, production 97.1 g, and water productivity 6.18 kg/m3 and was not significantly different from soil medium.